THE OCCURRENCE OF NORLUPANES AND BISNORLUPANES IN OILS OF TERTIARY DELTAIC BASINS - Curiale J.A. (My University, 2006)
Lupanoid hydrocarbons are known to occur in several petroleum systems, and lupane (C30) has recently been confirmed to exist in several crude oils. In contrast, norlupanes (C29) and bisnorlupanes (C28) are rarely observed in oil. All of these compounds are considered to derive from natural products of angiosperms, and numerous examples of their functionalized analogs are known. The occurrence of C28 and C29 lupanoids in biochemical and geochemical systems is reviewed here, and the presence and origin of their hydrocarbon analogs in crude oils are examined in detail. Although direct biochemical precursors for the lupane of crude oil are evident, such precursors for norlupane and bisnorlupane are not obvious. Nor is it clear if the C28 and C29 analogs are diagenetic descendants from the lupane structure. Adding additional confusion is the occurrence of these analogs in oils which show numerous indications of post-source molecular addition during migration and entrapment, making it unclear if they originate from a conventional source rock or from carrier or seal rock. Despite these uncertainties, there is extensive potential - some of which has already been realized - to use these compounds in oil-oil and oil-source rock correlations, particularly in instances where extensive biodegradation has occurred. Deconvolution of the time(s) of introduction of norlupane and bisnorlupane into the fluid - as well as various other hydrocarbons, including olefins - also provides great potential as a tool for mapping the migration history of an oil. © 2006 Elsevier Ltd. All rights reserved.